Aspirasi Karier Siswa SMA Berdasarkan Status Sosial Ekonomi dan Gender - Nunik Widiastuti (Universitas Mathla'ul Anwar Banten, 2017)
Career Aspirations of SMA Students Based Socio-Economic Status and Gender. This research is a descriptive study about career aspirations aimed to describe the career aspirations of students by socio-economic status and gender in SMA Negeri 1 Batujajar. The method used the quantitative descriptive method. Respondents in this study are students of class X SMA Negeri 1 Batujajar that are at the stage of self-orientation. At this stage people start selecting, establishing and looking for alternatives on the planning himself and his work. Selection of the sample using purposive sampling techniques so that the respondents in this study were 234 students. In general, the career aspirations of students 10.3% were in the low category, which is the category of being as much as 63.2%, and 26.5 % At the high category. Based on the socio-economic status of education last seen parents are in the moderate category. Based on parent income in middle category. Meanwhile, based on the gender ratio of the career aspirations of learners battery and men do not have a difference, with a probability value of 0.53.